2017
DOI: 10.12998/wjcc.v5.i2.27
|View full text |Cite
|
Sign up to set email alerts
|

Externalized conductors and insulation failure in Biotronik defibrillator leads: History repeating or a false alarm?

Abstract: Conductor externalization and insulation failure are frequent complications with the recalled St. Jude Medical Riata implantable cardioverter-defibrillator (ICD) leads. Conductor externalization is a “unique” failure mechanism: Cables externalize through the insulation (“inside-out” abrasion) and appear outside the lead body. Recently, single reports described a similar failure also for Biotronik leads. Moreover, some studies reported a high rate of electrical dysfunction (not only insulation failure) with Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Recently, isolated cases and single‐center and multicenter studies have reported that Biotronik Linox leads show high rates of electrical dysfunction and insulation failure of up to 12% at 5 years. The aim of this study was to compare the rate of lead failure in Linox Smart leads with that of two other leads: Endotak Reliance and Sprint Quattro Secure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, isolated cases and single‐center and multicenter studies have reported that Biotronik Linox leads show high rates of electrical dysfunction and insulation failure of up to 12% at 5 years. The aim of this study was to compare the rate of lead failure in Linox Smart leads with that of two other leads: Endotak Reliance and Sprint Quattro Secure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The conductor to the pace/sense ring electrode and the conductor coil to the RV defibrillation coil are located "decentered" in the lead isolation around the central conductor coil to the tip electrode. 4 Externalization of the shock coil could have led to short circuiting of current if interaction with the atrial lead had occurred and potentially low shock impedance and potentially ineffective shock. The attachment of the atrial lead tip helix likely contributed to electrical failure, through insulation damage, when the atrial lead was "snared" in the externalized conductor loop of the defibrillator lead.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is now well-known that ejection fraction alone has limited sensitivity and specificity as a risk marker for SCD, because it is not able to distinguish the risk of sudden death from death caused by heart failure or other non-cardiac diseases. Subsequently, many patients implanted for primary prevention according to current guidelines will have little benefit from their ICD, with a low rate of appropriate ICD therapy (2%-4%/year)[ 9 ], while they can suffer from side effects (even > 10%/year overall), in particular inappropriate shocks, lead failure and infections[ 10 , 11 ]. On the other side, many patients who are at risk of SCD are missed when using only LVEF, because the largest part of sudden arrhythmic death patients have only mildly depressed ejection fraction[ 9 , 12 , 13 ].…”
Section: Arrhythmic and Scd Risk Stratificationmentioning
confidence: 99%